Bond calls, credible commitment, and equity dilution: a theoretical and clinical analysis of simultaneous tender and call (STAC) offers - Dhillon, Upinder S.; Noe, Thomas H.; Ramı́rez, Gabriel G. (Journal of Financial Economics, 2001)
This paper is an exploration of the ability of game theory to explain real-world corporate maneuvering. We explore this issue by investigating bond tender offers accompanied by a threat to call nontendered bonds, so called “Simultaneous Tender and Call” (STAC) offers. We argue that STACs engender a transparent game played by bondholders and shareholders. We model this game and use this model to predict the outcome of STACs. Finally, we investigate the issue of whether this theoretical model explains the outcomes of four actual STAC issues made by James River, May Department Stores, and Houston Lighting & Power Company. Our clinical analysis provides support for the explanatory power of our model. Calibrating the predictions of the model with data from these STACs, we demonstrate a correspondence between theory and actual corporate behavior. As predicted by our model, subgame perfection, or threat credibility, and preplay coordination are central to explaining the outcomes of the STACs.